Deconstructed cat communities: quantifying the threat to felids from prey defaunation - Sandom, C; Williams, J; Hinks, A; Dickman, A; Burnham, D; Macdonald, E; Macdonald, D (Wiley, 2017)
Aim Defaunation, the emptying of ecosystems of fauna, has been highlighted as a likely threat to the conservation of carnivores but the magnitude of this threat has yet to be quantified. We quantify the potential threat defaunation presents to wild felids. Methods For the 32 wild felids that feed primarily on mammals, we used 5330 prey records from 237 published sources to compile a new diet dataset, FelidDIET. This dataset was used to determine the relative importance of the mammalian species as prey for each felid. These data were used to quantify the relationship between felid and prey species-richness, and to estimate the potential threat to wild felids from the loss of their prey. Results Our analyses reveal that models that include adjusted prey species-richness as a predictor of felid-richness out-perform those with less precise measures of prey-richness (potential prey-richness and total mammal-richness). This is true both when examined collectively or when split into those felids that prey upon large-bodied prey and those that prey upon small-bodied prey. For seven felid species, including six large felids (over 15kg), 33% or more of their primary prey-species are threatened. Of most concern is the Sunda clouded leopard Neofelis diardi, for which 66.0% of its primary prey-species are threatened. In total, 57.6% of large felids’ primary prey-species are threatened or declining, compared with 26.5% for small felids. Large felids are particularly vulnerable to primary prey decline in Indo-Malaya and East and Central Africa. Main conclusions Our findings indicate that imminent prey loss is likely to have substantial negative effects on large felids, many of which are already highly threatened. Considering the trophic cascades associated with large predators, the threat to large felids through the loss of prey diversity presents an ecosystem-scale threat.